(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The influence of Vitamin D on the progression of viral infections has become an area of increasing interest, particularly in the context of seasonal illnesses. This study aims to explore the relationship between Vitamin D levels and the severity of viral infections by comparing two groups: one with Vitamin D deficiency and the other with sufficient Vitamin D levels. Through this research, we aim to provide insights into the potential benefits of Vitamin D supplementation in managing viral infections.